A multi-agent-based system for two-stage scheduling problem of offshore project. (October 2017) - Han, Duanfeng; Yang, Boxin; Li, Jinghua; Wang, Jiaxuan; Sun, Miaomiao; Zhou, Qinghua
Aimed at enhancing the effectiveness and efficiency for offshore project scheduling, the mathematical model of two-stage scheduling is proposed according to the offshore project characteristics discussed in this article, which is used to solve the scheduling problem of large-scale and complex project. Regarding the two-stage scheduling, a system framework with multi-agent technology is presented to facilitate the integration and cooperation of offshore project scheduling. Next, the functional definition and internal structure of each intelligent agent is designed. Moreover, two kinds of intelligent algorithms have been designed to solve the resource conflicts and task assignment, respectively. Finally, the prototype system is developed to test the feasibility and rationality.